Informatization of Education in Kazakhstan: New Challenges and Further Development of Scientific Schools - Mynbayeva, Aigerim; Anarbek, Nazgul (International Review of Management and Marketing, 2016)
The purpose of the paper is to identify trends and systematize theoretical approaches developed in the theory of education of Kazakhstan; to review and summarize new global challenges, related to the informatization of education. The trends of the large-scale updating of the content of education, dinamizing of the education process, diversification of education within the framework of the mega trend of the informatization of education were identified. The problem of the transition from the generation of the twentieth century to a new generation, from receiving knowledge by reading or from a teacher's monologue to the visual perception, dialogue or polylogue in the audience, was put in the forefront. These challenges should be explored by scientists. The continuity of didactic paradigms was described: behaviorism → cognitivism→ constructivism → connectivism. It was found that about 30% of the scientific research in the field of education, conducted in Kazakhstan, are explicitly focused on the study of the informatization of education. More than 35% of thesis researches are also explicitly focused on studying IT as their subject. Scientific schools in the field of the informatization of education in Kazakhstan, covering different regions of the Republic, were listed and summarized. It was found that in the Republic there are virtually no studies on the psychological changes in thinking, memory, and attention in the process of active electronic and mobile teaching of a child. Keywords: Informatization of education, scientific schools, connectivism, digital technologies. JEL Classifications: I20, I23, I26